AML associated with previous cytotoxic therapy, MDS or myeloproliferative disorders: results from the MRC's 9th AML trial. - Hoyle, C; de Bastos, M; Wheatley, K; Sherrington, P; Fischer, P; Rees, J; Gray, R; Hayhoe, F (1989)
The outcome of treatment with standard first line therapy of 66 patients with acute myeloid leukaemia (AML) secondary to preceding chemotherapy (Group 1), a myelodysplastic state (Group 2) or a myeloproliferative disorder (Group 3) was analysed in relation to the preceding disorder, the cytogenetic pattern where available, and the cytology and cytochemistry of blood and bone marrow. The complete remission (CR) rate for the secondary AMLs was 36% (24/66), with 24% (16/66) dying in the induction period and 39% (26/66) having resistant disease. The CR rate was 25% (5/20) for Group 1, 42% (15/36) for Group 2, and 40% (4/10) for Group 3. Even after allowance for the generally older age of the secondary AML patients, they still had a significantly poorer CR rate than the de novo AMLs (P = 0.0004). The lower CR rate was chiefly due to resistant disease. Despite this, overall survival was not significantly worse for the secondary AML patients (P = 0.15). For the 36% that achieved remission, remission duration appeared similar to that of de novo cases. Of 62 cases with adequate cytology, 38 (61%) had evidence of erythroid and/or megakaryocytic dysplasia with a CR rate of 32% (12/38). The CR rate of these multineage leukaemias was not significantly different from that of the 24 (39%) who showed granulocyte/monocyte precursor involvement only, 42% (10) of whom achieved CR. The presence of features of differentiation within blast cells such as Auer rods or sudanophilia (greater than 50% positive blasts) was associated with a higher remission rate 47% (18/38) than that of poorly differentiated cases 17% (3/18) (P = 0.04) and thus appeared to be a more important determinant of CR achievement than was lineage involvement. Cases with a normal karyotype had a 33% (7/21) CR rate, while those with chromosomal abnormalities had a 37% (9/24) CR rate. Only 12 of the 45 cases with adequate cytogenetic analysis showed deletions or monosomies involving chromosomes 5 or 7, and seven of these were in Group 1.